Direct democracy in the European Union: how comparative federalism can help us understand the interplay of direct democracy and European integration - Mendez, Fernando; Mendez, Mario; Triga, Vasiliki (My University, 2009)
In recent decades Europe's political landscape has been marked by a notable rise in the use of mechanisms of direct democracy such as the referendum and the citizens' initiative. Our focus in this article is on the national referendums directly connected to the European Union (EU) integration process, a subject which is receiving increasing scholarly attention. Two interrelated questions are asked. First, how do these specific mechanisms of direct democracy interact with the existing federal political institutions of the EU? And, second, how does this affect the institutional stability of the EU polity? In addressing this problematique we undertake a cross-polity comparison of the EU-variant of direct democracy that reveals a range of institutional models and brings to the fore a neglected dimension in the study of EU referendum politics, the role of federal political institutions.
Keywords: Direct democracy; European Union; European integration; Federalism